Nicotinic acid test in the diagnosis of Gilbert's syndrome: correlation with bilirubin clearance. Issue 8 (August 1981) - Röllinghoff, W; Paumgartner, G; Preisig, R
Abstract : A provocation test with nicotinic acid (50 mg intravenously) was performed in 13 patients with Gilbert's syndrome and seven healthy volunteers to investigate the diagnostic value of several test parameters and to correlate them with the bilirubin clearance. The maximal increment of unconjugated serum bilirubin, the retention at four hours, and the area under the bilirubin concentration time curve. (AUC) were measured. Significant differences between patients and controls were found with regard to the AUC (7.95 +/- SD, 3.29 mmol/min/l vs. 3.08 +/- 0.57; P less than 0.001), the increment of unconjugated bilirubin (24.1 +/- 7.1 mumol/l vs. 10.2 +/- 3.2; P less than 0.001) and the retention (77.7 +/- 8.9% vs. 45.8 +/- 27.4%; P less than 0.02). Of those, the AUC discriminated best between patients and controls. Five patients with Gilbert's syndrome had normal serum bilirubin concentrations (less than 17.1 mumol/l = 1 mg%) at the time of the study, but abnormal AUC and bilirubin increment. A significant correlation was found between the bilirubin clearance and the retention (r = -0.96; P less than 0.001) as well as the AUC (r = -0.82; P less than 0.05) but not with the bilirubin increment. This simple test may be used to assess the disturbance of bilirubin clearance in Gilbert's syndrome.